Ru Jiao: Traditional Sports of Taijiquan, Archery, and Wu Shu - Afat, Afat (Yayasan Insan Mulia Bima, 2025)
This journal explores the relationship between Confucian teachings and traditional Chinese sports, specifically Taijiquan (Tai Chi), archery, and Wushu. The study examines how Confucian principles such as balance, self-discipline, and moral character development are reflected in these sports practices. Taijiquan combines physical movements with meditation to achieve harmony between body and mind. Archery is used as a tool to develop virtues like patience and self-control. Wushu emphasizes the importance of ethics and spiritual development. A literature review method was used to analyze relevant sources, showing that traditional Chinese sports not only improve physical health but also play a crucial role in the development of moral and spiritual character. The integration of Confucian teachings into traditional Chinese sports can significantly contribute to enhancing the quality of life in society through moral development, balance, and discipline.